Case Report: Application of controlled pericardial drainage in type A aortic dissection complicated by cardiac tamponade - He, Yixin; Yang, Ying (Frontiers in Cardiovascular Medicine, 2025)
BackgroundType A aortic dissection (TAAD) complicated by cardiac tamponade represents a life-threatening cardiovascular emergency. Acute pericardial effusion can severely compromise cardiac function. Although emergent surgical repair remains the gold standard, preoperative hemodynamic instability substantially increases surgical risk. Controlled pericardial drainage (CPD) has been proposed as a bridging intervention to rapidly relieve tamponade symptoms while mitigating the complications associated with excessive drainage. However, its clinical utility remains controversial because of concerns that the elevation in post-drainage blood pressure may accelerate dissection progression or trigger rupture. This case report highlights the successful use of CPD to stabilize a patient with TAAD and cardiac tamponade, facilitating a safe transition to definitive surgery. It also discusses the clinical utility of this strategy.Case presentationA 48-year-old man presented to the emergency department with an acute onset of altered mental status lasting 50 min. Bedside ultrasound and aortic computed tomography angiography confirmed a TAAD diagnosis complicated by pericardial tamponade. After the examination, the patient experienced sudden hypotension, which was promptly managed with emergency CPD, resulting in rapid stabilization of blood pressure. Subsequently, the patient underwent “Sun's procedure” and artificial vascular replacement, during which 500 mL of pericardial blood was extracted. The patient recovered well and was discharged 24 days after the surgery.ConclusionWith rigorous hemodynamic monitoring and a multidisciplinary framework, CPD effectively functions as a preoperative stabilization approach in patients with TAAD complicated by pericardial tamponade, securing valuable time for subsequent surgical interventions.